2006
DOI: 10.1080/00016340600605044
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and anthropomorphic risk factors for shoulder dystocia

Abstract: Shoulder dystocia may be anticipated in cases involving short women and discrepancy between maternal height or weight and infant weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 21 publications
0
29
2
3
Order By: Relevance
“…Mazouni et al stated that obesity is a significant maternal risk factor for shoulder dystocia, but also specified that the risk is caused by discrepancy between maternal height or weight and infant weight [22]. In contrast, Robinson et al found that obesity cannot be seen as an independent risk factor and they stated that fetal macrosomia is the single most powerful predictor in their study [23].…”
Section: Discussionmentioning
confidence: 94%
“…Mazouni et al stated that obesity is a significant maternal risk factor for shoulder dystocia, but also specified that the risk is caused by discrepancy between maternal height or weight and infant weight [22]. In contrast, Robinson et al found that obesity cannot be seen as an independent risk factor and they stated that fetal macrosomia is the single most powerful predictor in their study [23].…”
Section: Discussionmentioning
confidence: 94%
“…Consequently, persistent brachial palsy with irreversible changes found in about 3% of patients one year after birth, with recovery in upper brachial palsy possible in about 80% (Duchen-Erb) and in lower in 40% of cases (Klumpke). About 40% of SD appears in children with birth weight below 4000g, although fetal macrosomia in babies with birth weight above 4000-4500g is also a predicting factor for development of SD, usually because of relative fetopelvine disproportion [9,10]. Injuries in newborns tend to develop as a consequence of any of the following two conditions -either protracted shoulder incarceration (hypoxia/ acidosis), or complications as a consequence of hand maneuvers (uncritical head and neck tractionspinal cord injury without radiographic abnormalities /SCIWORA/, brachial palsy, injuries of neck organs).…”
Section: Discussionmentioning
confidence: 99%
“…This finding implies that inadequate screening for glucose intolerance and superficial treatment of diabetes are conducive to these injuries. This being the case, implementation of the proposed measures could probably reduce the rate of shoulder dystocia markedly both in America and in other countries, where its rate has also increased in recent years [1,9,[33][34][35][36]. The "CESDI Committee", having investigated shoulder dystocia related fetal deaths in England, Wales and Northern Ireland, found substandard intrapartum management the most frequent causative factor [3].…”
Section: Discussionmentioning
confidence: 99%